Combined PBL and PhET simulation for critical thinking in mathematical reasoning and problem-solving skills - Lailiyah, Siti; Kusaeri, Kusaeri; Asmiyah, Siti; Naryaningsih, Putri Dwi; Dina, Anni Mujahidad; Irmanila, Elmita (Journal of Education and Learning (EduLearn), 2026)
Students’ critical thinking (CT) in mathematical reasoning and problem-solving (PS) skills has not developed. In fact, these skills determine achievement in society 5.0. Therefore, learning models and media are needed to develop both. This study investigated the interaction of variables in problem-based learning (PBL) combined with play mathematics with technology (PhET) simulations for CT and PS skills. This study used quasi-experimental research design using questionnaires and test of CT and PS involving 126 students of grade V of Islamic primary school (Madrasah Ibtidaiyah (MI)) and grade IX of Islamic junior high school (Madrasah Tsanawiyah (MTs)). Factorial analysis of the data used SmartPLS. Based on cross loading value, the MI level shows positive interactions on variable: “happy”, “easy to use”, and “as new thing” of PS skills (the explore and plan (EP), select a strategy (SaS), and find an answer (FaA) indicators) and CT skills (the recognition of assumption (RoA) indicator). At the MTs level shows positive interaction on PS skills (the read and think (RT) indicator) and CT skills (the inference (In) and interpretation (Int) indicators) on the “easy to use the PhET simulation” variable. Our findings highlight that combined PBL and PhET simulation has a significant relationship to develop students’ CT and PS skills.